PENGARUH PERNIKAHAN DINI TERHADAP KUALITAS PENDIDIKAN INFORMAL PADA KELUARGA HINDU DI KOTA MATARAM - Luh Apriani (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
Abstract This study aims to analyze the quality of informal education in the Hindu family environment of early marriage perpetrators in the city of Mataram. Departing from the phenomenon that many early marriages take place due to matchmaking factors, promiscuity, or blind love which often causes problems for the perpetrators in living household life. The problem is not only felt by the husband/wife, but the children born in the family also feel the impact through parenting that is accepted as a form of informal education. This study uses qualitative methods with data obtained through observation, interviews and documentation studies. The research focuses on six sub-districts, Ampenan, Sekarbela, Mataram, Selaparang, Cakranegara and Sandubaya, all locations are located in Mataram City. From the results of the study, it was found that the people of Mataram had a less favorable perception of the practice of early marriage. This is inseparable from the fact that many families who do early marriage experience problems financially, emotionally and in readiness. Then related to the psychological impact, the psychological impact is more likely to be felt by the wife (woman) and children. For the wife, the psychological impact felt in the form of anxiety, stress, emotions became unstable and made marriage a burden. Meanwhile, for children, the psychological impact felt in the form of not being able to control themselves, being introverted, not daring to innovate and not daring to make decisions. While related to the quality of informal education in Hindu families who do early marriage, it is illustrated that the informal education process is less than optimal, the cultivation of religious values, character, ethics, morals, manners and social skills is lacking as a result of permissive parenting.